A Performance Analysis of Electric Power Transmission Systems Using Ultra-High Voltage Direct Current (UHVDC) Technology - Miftah Hadi R Harahap; Zuraidah Tharo; Parlin Siagian (Sean Institute, 2026)
The increasing demand for electrical energy and the growing distance between power generation sources and load centers require transmission systems capable of delivering large amounts of power efficiently and reliably. Ultra-High Voltage Direct Current (UHVDC) technology has emerged as an effective solution for long-distance, high-capacity power transmission, offering lower power losses and higher efficiency compared to conventional transmission systems. This study aims to analyze the performance of electric power transmission systems using UHVDC technology, identify factors affecting system performance, and evaluate the impact of transmission distance on system efficiency and reliability. The research employs a quantitative descriptive approach through modeling and simulation of a UHVDC transmission system. Key performance parameters analyzed include power losses, transmission efficiency, voltage stability, and power transfer capability under various transmission distance scenarios. The results indicate that UHVDC systems are capable of transmitting large-scale power over long distances with relatively low power losses. Although increasing transmission distance leads to higher power losses, the rate of increase is significantly lower than that of conventional alternating current (AC) transmission systems, allowing UHVDC systems to maintain high efficiency. Furthermore, the UHVDC system demonstrates good voltage stability and operational reliability when operating within its design limits. Based on the findings, it can be concluded that UHVDC technology is a reliable and efficient solution for long-distance, high-capacity power transmission and has strong potential to support large-scale renewable energy integration and the development of modern power system infrastructure.